Enhanced Security using Secure Multiparty Computation to E-voting application in cloud - Kishor Chaudhari, Umang; Vijaya Kumar, A; Venkata Sai, G (International Journal of Engineering and Technology, 2018)
Secure outsourcing of computation on sensitive data is an important topic that has received a lot of attention recently. E-Voting system is interested in method collaboration system to ameliorate the quality of System. Cloud computing is integrating in communication and information technologies in the E-Voting. In fact, the paradigm is to provide the computational resources or result at the end of the services. Further it needs to reveal the voting information result but if faces several challenges in the security it must be overcome without reveal any sensitive data to unauthorized parties. To accomplish this objective, we proposed secure multiparty computation techniques (SMC). The main aim of our work is to use the suitable model for parties to together compute their function based on their inputs without revealing their private inputs. The idea behind is the several collaborate system use to their shared objectives without allow any gathering to information and private information.Â Â